Induction of apoptosis and G2/M arrest by ampelopsin E from Dryobalanops towards triple negative breast cancer cells, MDA-MB-231 - Abd Rahman, Napsiah; Saiful Yazan, Latifah; Wibowo, Agustono; Ahmat, Norizan; Foo, Jhi Biau; Tor, Yin Sim; Yeap, Swee Kong; Razali, Zainal Abidin; Ong, Yong Sze; Fakurazi, Sharida (BioMed Central, 2016)
Background: Several compounds isolated from Dryobalanops have been reported to exhibit cytotoxic effects to several cancer cell lines. This study investigated the cytotoxic effects, cell cycle arrest and mode of cell death in ampelopsin E-treated triple negative cells, MDA-MB-231. Methods: Cytotoxicity of ampelopsin E, ampelopsin F, flexuosol A, laevifonol, Malaysianol A, Malaysianol D and nepalensinol E isolated from Dryobalanops towards human colon cancer HT-29, breast cancer MDA-MB-231 and MCF-7, alveolar carcinoma HeLa and mouse embryonic fibroblast NIH/3 T3 cells were determined by MTT assay. The cells were treated with the compounds (0.94–30 μM) for 72 h. The mode of cell death was evaluated by using an inverted light microscope and annexin V/PI analysis. Cell cycle analysis was performed by using a flow cytometer. Results: Data showed that ampelopsin E was most cytotoxic toward MDA-MB-231 with the IC50 (50 % inhibition of cell viability compared to control) of 14.5 ± 0.71 μM at 72 h. Cell shrinkage, membrane blebbing and formation apoptotic bodies characteristic of apoptosis were observed following treatment with ampelopsin E. The annexin V/PI flow cytometric analysis further confirmed that ampelopsin E induced apoptosis in MDA-MB-231 cells. Cell cycle analysis revealed that ampelopsin E induced G2/M phase cell cycle arrest in the cells. Conclusion: Ampelopsin E induced apoptosis and cell cycle arrest in MDA-MB-231 cells. Therefore, ampelopsin E has the potential to be developed into an anticancer agent for treatment of triple negative breast cancer.